Social capital and the integration of processes in the supply chain management in the real sector in Colombia - Aldana Bernal, Juan Carlos (2019)
This research evaluates the relationship of social capital with the integration of processes in the supply chain management in companies of the real sector in Colombia, mediated by their organizational size and the uncertainty of the environment. For this purpose, 232 companies associated to the real sector in Colombia were surveyed and with the information obtained, multivariate analysis of structural equations was made with the SPSS and AMOS tools. As a result, there is a significant direct relationship between social capital and the integration of processes in the supply chain management, thus social capital was identified as a fundamental determinant in efforts to integrate the supply chain, unlike the mediating variables analyzed (size and uncertainty of the environment).